2014
DOI: 10.1111/jnc.12760
|View full text |Cite
|
Sign up to set email alerts
|

GM1 ganglioside enhances Ret signaling in striatum

Abstract: It has been proposed that GM1 ganglioside promotes neuronal growth, phenotypic expression, and survival by modulating tyrosine kinase receptors for neurotrophic factors. Our studies tested the hypothesis that GM1 exerts its neurotrophic action on dopaminergic neurons, in part, by interacting with the GDNF (glia cell-derived neurotrophic factor) receptor complex, Ret tyrosine kinase and GFRa1 coreceptor. GM1 addition to striatal slices in situ increased Ret activity in a concentration-and time-dependent manner.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 81 publications
(297 reference statements)
0
17
0
Order By: Relevance
“…other gangliosides besides GM1 to activate Trk when applied to intact striatal tissue (Duchemin et al, 2002). A recent report indicated that chronic GM1 application enhanced RET activity and phosphorylation in the striatum of MPTP-treated mice while promoting recovery of DA and DOPAC deficits (Newburn et al, 2014), consistent with the suggestion that applied GM1 may function as a GDNF mimetic. The experimental paradigm employing exogenous GM1, which may underlie the symptomatic improvements reported in PD clinical trials (Schneider et al, 2010(Schneider et al, , 2013, does not, in our opinion, reveal the functional role of GM1 in regard to normal GDNF signaling.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…other gangliosides besides GM1 to activate Trk when applied to intact striatal tissue (Duchemin et al, 2002). A recent report indicated that chronic GM1 application enhanced RET activity and phosphorylation in the striatum of MPTP-treated mice while promoting recovery of DA and DOPAC deficits (Newburn et al, 2014), consistent with the suggestion that applied GM1 may function as a GDNF mimetic. The experimental paradigm employing exogenous GM1, which may underlie the symptomatic improvements reported in PD clinical trials (Schneider et al, 2010(Schneider et al, , 2013, does not, in our opinion, reveal the functional role of GM1 in regard to normal GDNF signaling.…”
Section: Discussionmentioning
confidence: 74%
“…The ability of LIGA20 to restore a functional receptor complex is somewhat analogous to the restorative association of this analog with a nuclear Na + /Ca 2+ exchanger in GM1-deficient mice (Wu et al, 2005), such association occurring intraneuronally as was also the case with the TrkA-GM1 association (Mutoh et al, 2002). The prolonged benefit of LIGA20 (Wu et al, 2012) compared to the transient effect of exogenous GM1 (Duchemin et al, 2002;Newburn et al, 2014) suggests that two fundamentally different mechanisms are at work.…”
Section: Discussionmentioning
confidence: 94%
“…GDNF is required for survival of dopaminergic neurons, and GM1 is important for proper GDNF signaling (Hadaczek et al, 2015). GM1 associates with the GFR 1 and RET components of the tripartite GDNF receptor and is required for its assembly (Hadaczek et al, 2015;Newburn et al, 2014). Mice null for B4galnt1, the gene that codes for N-acetylgalactosamine transferase (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous GM1 has been shown to inhibit aggregation of α-synuclein in vesicle cultures and prevent destruction of dopaminergic neurons in the SNc after MPTP exposure (Fazzini et al , 1990; Hadjiconstantinou et al , 1989; Martinez et al , 2007). One mechanism by which GM1 exerts neurotrophic effects on dopaminergic neurons is by enhancing glial cell-line-derived neurotrophic factor (GDNF) signaling through the “rearranged during transcription” (RET) receptor tyrosine kinase and GDNF family receptor α1 (GFRα1) components of the GDNF receptor complex (Hadaczek et al , 2015; Newburn et al , 2014). GM1 has also been demonstrated to be effective in clinical studies with Parkinson’s patients (Schneider, 1998; Schneider et al , 1995, 2010, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation